Greek Thrace and the Archaic Period Thassian peraia: interaction, dialogue, contact and network in Northern Aegean - Juliana Figueira da Hora (História, 2022)
Abstract It is our objective, in this article, to present geographical and historical aspects of South Western Thrace and the island of Thassos, as well as to bring up and highlight the interaction between continent and island. Thassos has a marked proximity to the continent and, according to archaeological sources1, a close relationship between the island and the region of Thrace since the Neolithic period can be established. With the arrival of the Greeks, in the Archaic Period, the fluidity of the contact between continent and island solidified with the foundation of Thassian settlements within Thracian territory. This relationship was marked by intense commercial and social exchanges and local and regional interactions in the Northern Aegean in the Archaic Period.